2008
DOI: 10.2139/ssrn.1311890
|View full text |Cite
|
Sign up to set email alerts
|

Small is Beautiful: Evidence of an Inverse Relationship Between Farm Size and Yield in Turkey

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…The analysis of factors influencing the variation in yield gap within farmers' fields revealed an inverse size-yield relationship, implying that there was a tendency towards increasing yield gap with the increasing landholding size, which was attributed to an inverse relationship between landholding size and apple yield. This finding is consistent with the findings of the studies conducted elsewhere (Niroula and Thapa 2007;Ünal 2008;Sial et al 2012;Aneani and Ofori-Frimpong 2013). The inverse size-yield relationship is attributed to the fact that small farmers could take care of apple orchards properly by virtue of availability of higher household labor per unit of land.…”
Section: Discussionsupporting
confidence: 93%
“…The analysis of factors influencing the variation in yield gap within farmers' fields revealed an inverse size-yield relationship, implying that there was a tendency towards increasing yield gap with the increasing landholding size, which was attributed to an inverse relationship between landholding size and apple yield. This finding is consistent with the findings of the studies conducted elsewhere (Niroula and Thapa 2007;Ünal 2008;Sial et al 2012;Aneani and Ofori-Frimpong 2013). The inverse size-yield relationship is attributed to the fact that small farmers could take care of apple orchards properly by virtue of availability of higher household labor per unit of land.…”
Section: Discussionsupporting
confidence: 93%
“…However, Lahore and Mianwali districts were found middle ranked in the overall ranking of the districts in the province. The districts having a large number of small farmers, perhaps, have tilled more intensively as compared to others and have proven the decades' old famous concept of the inverse relationship in the agricultural sector (Unal, 2008). Table 4 describes the ranking of the percentage of land ownership titles (percent ALO) in all districts of the province.…”
Section: Resultsmentioning
confidence: 99%
“…As no such relationship could be found in the literature, specifically regarding Gini of operational land holdings and food insecurity, we may use farm productivity as a proxy of food security in relation to land inequality. Abundant literature is available expressing the negative impact of land inequality on farm productivity (Ali & Deininger, 2013;Anyaegbunam, Nto, & Madu, 2012;Mahmood & Jahnke, 2010;Unal, 2008) and (Vollrath, 2012), which contradicts the results of this particular model-I. Moreover, the results of percentage of land ownership titles are in line with the conclusions of Fedrer (1987) and Lee (2011) while the results of this study contradict Matchaya's (2010) conclusions, who found no evidence for the rise in farm productivity due to a rise in land ownership in Malawi.…”
Section: Regression Analysismentioning
confidence: 99%
“…However, no study could be traced in the literature outlinging the relationship of food security and Gini of operational farmland holding. However, if farm productivity or total factor productivity is regarded as proxy for food security, then abundant literature (Niroula and Thapa, 2005;Vollrath, 2006;Unal, 2008;Anyaegbunam et al, 2012;Ali and Deininger, 2015;Sheng et al, 2015) is available, indicating an inverse association between farm size and its corresponding productivity per unit area. In this context, operational farm holdings having a positive relationship with food security under brief study provides contrary evidence to these earlier studies.…”
Section: Estimation Of Econometric Modelsmentioning
confidence: 99%